The Effect of Yoga Exercise on the Menstrual Cycle - Asmalinda, Wita; Sapada, Edy; Darma, Lidrian Arifan (Poltekkes Kemenkes Palembang, 2025)
Irregular menstrual cycles are a problem that generally occurs in teenage girls. The prevalence of menstrual cycle disorders is 16.4%. Yoga practice focuses on the body's biomechanics by maximizing musculoskeletal and spinal mechanics. Stretching sessions can slowly relax the body's muscles following a calm breathing rhythm. Practicing yoga regularly can enhance concentration and alleviate anxiety. This study aimed to analyze the effect of yoga practice on improving the menstrual cycle. This type of research is an experiment with a comparison group. The sampling method used was simple random sampling. The research was conducted over 30 days, with the research subjects being students from Palembang 6 State High School. The number of respondents was 50 people, divided into two groups. Yoga practice is the independent variable, and the menstrual cycle is the dependent variable. The average result of the menstrual cycle before treatment was 1.24+0.523 and after treatment was 1.08+0.277, with a mean difference of 0.16, with a p value of 0.000. The results of the independent analysis test for the mean value of the treatment group and the control group were 1.04+0.200 with a mean difference of 0.04, and a value of p=0.046 was obtained. The null hypothesis was rejected, meaning there was a significant difference in the menstrual cycle between the yoga practice groups. So it can be concluded that yoga practice is effective in improving the menstrual cycle. It is recommended that further research be conducted on cytokine parameters.